APPOINTMENTS OFARBITERS IN INDONESIAN NATIONAL BOARD OF ARBITRATION IN CIVIL CASEBASED ON LAW OF THE REPUBLIC OF INDONESIA NUMBER 30 OF 1999 CONCERNING ARBITRATION AND ALTERNATIVE DISPUTE RESOLUTION - Ayi Nurjanah (JURNAL HUKUM DE'RECHTSSTAAT, 2018)
This study aims to find out application and effectiveness of Law no. 30 of 1999 on the Indonesian National Board of Arbitration (BANI) of South Jakarta, especially regarding the mechanism of its  implementation of arbitral tribunal elections and their impact on  settlement of arbitration dispute on the institution, and to know the obstacles that hinder the success of arbitration. This research is normative juridicial with the approach of legislation and analytical approach. Data collection techniques are field studies through interviews with related parties. Research data consist of primary and secondary data. Primary data were obtained by direct interviews using structured interview guidelines. Meanwhile,, the secondary data obtained by reviewing documents and literature related to the object of research. Then such data is obtained and is analyzed qualitatively by explaining the problems as discussed in the thesis. From the results of the study, what can be concludedthat: (1) measures the election and appointment of arbitrators is proven effective due to its large impact on the settlement of the dispute so that it can be done more quickly than the general courts. (2) Based on the authority of the arbitrators,  an effortto implement Law No. 30 of 1999 has been well implemented as stipulated in the regulation, but there are still factors that hinder the success of arbitration to BANI  which come from the parties, arbitrator's inability, high cost of arbitration and public knowledge about unpopular arbitration institution.